Analisis StrukturChassis Mobil Listrik Enggang EVO Terhadap Beban Statik - Alfian Djafar; Widya Hadiprasetiyo (Universitas Muhammadiyah Semarang, 2020)
Electric cars are one alternative vehicle to overcome the problem of fuel oil scarcity. One aspect to be considered in the design of electric cars is the safety and comfort of the driver to avoid serious injury in case of accident. Chassis is one of the most important components of the vehicle, because it serves as a weight support vehicle, engine, and driver and passengers Because the chassis will receive the load, it is necessary to do analysis by Finite Element Analysis. The purpose of this research is to know the effect of stress on chassis and safety factor value due to stress with material AISI 310 and ASTM A36. The method used is the simulation of chassis to passenger load, engine load, front collision load, rear crash load, and side collision load. After the simulation the chassis safely receives the passenger load and engine load. Simulation results of front, rear and side collision loads show that the chassis is not safe to load, so redesign must be done. Redesign is done by increasing the number of bars on the chassis to reduce the working sitress. The chassis simulation results after the redesign show the chassis safely accept front, rear, and side impact loads.